SCIENCE IN THE EARLY ROMAN EMPIRE ([S.l.])
1 online resource
Keywords: The studies collected in Science in the Early Roman Empire (1986) represent key research done on the Elder Pliny - an important and difficult figure whose Natural History forms a valuable compendium at a fixed historical point in time of ancient science. Its subsequent influence was enormous, remaining the most comprehensive scientific encyclopaedia even until the Renaissance. The chapters seek to locate Pliny in his social and intellectual milieu, to survey his approach to particular sciences such as astronomy, mineralogy, botany and pharmacopoeia. Two chapters consider the response in the Renaissance to his work.